Prostatic leiomyoma: A case report - Manoj Kumar Deepak; Muthu Veeramani (Urology Case Reports)
A pure leiomyoma of the prostate, a rare tumor with fewer than 30 documented cases, typically initiates as focal points within the gland, causing prostatomegaly. Pathological examination is crucial for diagnosis, distinguishing it from leiomyosarcoma. Complete tumor resection is preferred, with methods like transurethral resection, open adenomectomy, or prostatectomy. Here, we detail a 72-year-old male's case of prostatic leiomyoma, treated via Robotic prostatectomy, highlighting the importance of accurate diagnosis and tailored therapy for this rare condition.